2016
DOI: 10.5694/mja15.01360
|View full text |Cite
|
Sign up to set email alerts
|

Health care variation: time to act

Abstract: Summary Geographic variation in health care use has been demonstrated in many countries over many years. Such variation can be warranted — in response to patient need or preference for care — or unwarranted. Unwarranted variation raises concerns about equity and appropriateness of care. Recent analyses of health care provision in the Australian atlas of healthcare variation show that when routinely available Australian data are mapped by residence of patient, there are wide variations in rates of use of diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…As a result, this makes the reliability of applying extracted data questionable in a clinical audit. Buchan et al (2016) noted the implications of incomplete data or inconsistency in coding were that it can create unnecessary variations in care, with Duggan et al (2016) suggesting that this can lead to real patient harm due to patients not receiving the right care. The Australian Commission on Safety and Quality in Health Care (2012) reported that the data used to measure the occurrence of problems in health care is unavailable or unreliable, and patient safety is probably more difficult to assess due to the lack of systematic approaches to identify issues (Phillips et al 2010b).…”
Section: Review Of Literature On Similar Casesmentioning
confidence: 99%
“…As a result, this makes the reliability of applying extracted data questionable in a clinical audit. Buchan et al (2016) noted the implications of incomplete data or inconsistency in coding were that it can create unnecessary variations in care, with Duggan et al (2016) suggesting that this can lead to real patient harm due to patients not receiving the right care. The Australian Commission on Safety and Quality in Health Care (2012) reported that the data used to measure the occurrence of problems in health care is unavailable or unreliable, and patient safety is probably more difficult to assess due to the lack of systematic approaches to identify issues (Phillips et al 2010b).…”
Section: Review Of Literature On Similar Casesmentioning
confidence: 99%
“…Moreover, employing the domains of STEEEP may reduce variation in how care is delivered and practiced, revealing differences that exist across geographic, cost, and personal (e.g. racial) characteristics [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, numerous studies have evaluated the factors that lead a patient with CLBP to seek professional help (Buchan, Duggan, Hargreaves, Scott, & Slawomirski, 2016;IJzelenberg & Burdorf, 2004;Traeger, Buchbinder, Elshaug, Croft, & Maher, 2019). Research has shown that there is a positive association between care seeking and sociodemographic variables such as age, PeerJ reviewing PDF | (2019:08:40707:2:0:CHECK 5 Feb 2020)…”
Section: Introductionmentioning
confidence: 99%